Metatexte. Erzählungen von schrifttragenden Artefakten in der alttestamentlichen und mittelalterlichen Literatur - Ott, Michael R. (Materiale Textkulturen, 2016)
Texts of the Old Testament and the literature of the European Middle Ages feature a number of narratives about objects on which something is written. In this volume, scholars from the fields of Old Testament studies, Jewish studies, and medieval literary studies examine approaches for analyzing such stories and their narrating and narrated objects.